Extensive and widespread homologies between mitochondrial DNA and chloroplast DNA in plants - Stern, David B. (1984)
We used hybridization techniques to demonstrate that numerous sequence homologies exist between cloned mung bean and spinach chloroplast DNA (ctDNA) restriction fragments and mtDNAs from corn, mung bean, spinach, and pea. The strongest cross-homologies are between clones derived from the ctDNA inverted repeat and mtDNA from corn and pea, although all the ctDNA clones tested hybridized to at least one mtDNA restriction fragment. Known chloroplast genes showing strong mtDNA homologies include those for the large subunit of ribulosebisphosphate carboxylase, which hybridizes to corn mtDNA, and the β subunit of the chloroplast ATPase, which hybridizes to mung bean mtDNA. Certain of these homologies were confirmed by using cloned spinach mtDNA restriction fragments as probes in reciprocal hybridizations to ctDNA. Several of these ctDNA-homologous mtDNA sequences were shown to be much more closely related to ctDNA from the same species than to that of a distantly related species. We interpret these differential homologies as evidence for relatively recent DNA sequence transfer events, suggesting that transpostion between the two genomes is an ongoing evolutionary process.